2021
DOI: 10.3855/jidc.13926
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear link between temperature difference and COVID-19: Excluding the effect of population density

Abstract: Introduction: The spatiotemporal patterns of Corona Virus Disease 2019 (COVID-19) is detected in the United States, which shows temperature difference (TD) with cumulative hysteresis effect significantly changes the daily new confirmed cases after eliminating the interference of population density. Methodology: The nonlinear feature of updated cases is captured through Generalized Additive Mixed Model (GAMM) with threshold points; Exposure-response curve suggests that daily confirmed cases is changed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…However, some studies used non-linear models to deal with the relationship between Covid-19 and some non-demographic variables. For example, [ 52 ] identified a significant non-linear link between temperature difference and Covid-19 in the case of the United States. Another study [ 53 ] focused on 65 countries of the world and examined the nonlinear relationship between Covid-19 cases and carbon damages, managing financial development, renewable energy consumption, and innovative capability.…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies used non-linear models to deal with the relationship between Covid-19 and some non-demographic variables. For example, [ 52 ] identified a significant non-linear link between temperature difference and Covid-19 in the case of the United States. Another study [ 53 ] focused on 65 countries of the world and examined the nonlinear relationship between Covid-19 cases and carbon damages, managing financial development, renewable energy consumption, and innovative capability.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have failed to correct for the discrepancies that existed in the data reported from different regions, all of which may lead to uncertainty in the analysis results. Recently, an increasing number of studies have used non-linear time series analysis methods, such as GAM [ 5 , 23 , [38] , [39] , [40] , [41] , [42] , [43] , [44] ] and DLNM [ 28 , [44] , [45] , [46] ]. However, these studies encompass analyses at the country [ 43 , 44 ], state [ 5 , 26 , 40 ] or city [ 23 , 28 , 38 , 39 , 41 , 45 , 46 ] level.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies have used non-linear time series analysis methods, such as GAM [ 5 , 23 , [38] , [39] , [40] , [41] , [42] , [43] , [44] ] and DLNM [ 28 , [44] , [45] , [46] ]. However, these studies encompass analyses at the country [ 43 , 44 ], state [ 5 , 26 , 40 ] or city [ 23 , 28 , 38 , 39 , 41 , 45 , 46 ] level. In studies with a country or state as the unit of analysis, the regional scope is relatively large, and acquiring data on meteorological indicators and their representativeness is prone to significant errors.…”
Section: Introductionmentioning
confidence: 99%
“…Short panel datasets, where the stimulus of interest has a limited range (temperature, humidity, UV light, air pollution in each location), often lack the statistical power to pin down such response functions. Consequently, estimated response functions frequently have conflicting signs on key variables or are fragile in the sense that statistical significance is gained or lost when time trends or demographic variables are added to models (Briz-Redón and Serrano-Aroca 2020 ; Ding et al 2021 ; Jamshidi et al 2020 ; Jüni et al 2020 ; Kerr et al 2021 ; Mecenas et al 2020 ; Pedrosa 2020 ; Xu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%